Is befriending a possible intervention in people living with schizophrenia? - Iftene, Felicia; Farcas, Adriana; O’Brien, Simon (Frontiers in Psychiatry, 2025)
IntroductionBefriending is a non-specific intervention that may be valuable, cost-effective and easy to implement, complementing the complex therapeutic approach that schizophrenia requires.ObjectivesThis is a prospective, repeated-measures study design aimed to evaluate the possible clinical and functional changes in people living with schizophrenia undergoing 4 individual-basis, weekly Befriending sessions. The chart reviews supplemented the demographic information.MethodsParticipants: 32 individuals with a diagnosis of schizophrenia or schizoaffective disorder were enrolled in this study. Specific psycho-social instruments were used to assess the possible clinical and/or functional changes post-intervention.Results/discussionsNo statistically significant clinical improvement was found at the end of the intervention. However, we found a statistically significant improvement in quality of life, as measured by the Q-LES-Q-SF questionnaire, and a statistically significant decrease in the Anxiety item on the PANSS General Scale.ConclusionsBefriending was identified as providing an opportunity for increased social interactions and the development of healthy social relationships, suggesting that it may be considered a complementary or supplementary intervention for patients with schizophrenia, especially when CBTp is not readily available. A protocol involving the use of befriending as a pre-CBT intervention tool was suggested as a preparatory stage addressing social and interactional skills necessary for the more involved therapeutic engagement of the CBTp.